A Research on the Opinions Related to the Personality Traits and Affect-States of Psychological Counselor Candidates through “Draw a Picture of Cactus Test" - Gamze Mukba (Muhammed Yıldız, 2018)
“Draw a Picture of Cactus Test” is among the reflective tests; and can contribute to knowledge acquisition about both children and adults’ inner world, personality traits and affect-state. In this research, it is aimed to reveal the opinions related to their personality traits, affect-state and inner state of psychological counselor candidates through “Draw a Picture of Cactus Test”. The participants of the research are 6 males and 15 females, totally 21 participants who are at the first and the second class of Psychological Counseling and Guidance Department in Van Yüzüncü Yıl University in 2017-2018 Academic Year. This research is qualitative and its data has been collected via semi-structured interview technique. According to the results, some of the female participants and all male participants have drown “a wild cactus picture” have not drown a pot and in this regard; it can be said that they are “keen on independence”. Hence, the pictures of cactuses in the pot and the ones have roots are associated with being home-loving; the pictures of the desert cactuses, wild cactuses are associated with ‘being independent’. In this context, it can be said that male students participated in this research do not have home-loving temperament. By this application, it is deduced that via the pictures drawn by the individuals, important knowledge about their affect state and inner world can be obtained.